2017
DOI: 10.1007/s40097-017-0233-6
|View full text |Cite
|
Sign up to set email alerts
|

Production of functional graphene by kitchen mixer: mechanism and metric development for in situ measurement of sheet size

Abstract: It has been reported that the production of defect free graphene is possible by the application of a kitchen mixer. Yet, we note that the natural-surfactant role in the exfoliation mechanism by a kitchen mixer has rarely been discussed. To investigate the possibility of graphene exfoliation in a bio-surfactant medium, we have produced graphene from the co-mixing of graphite and gum Arabic. Through the modelling of bulky graphite as a single composite disc, we have shown that the exfoliation of graphite crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…However, for the production of large quantities, a cost-effective and environmentally friendly system is very important. Considering this fact, liquid-phase exfoliation has attracted the attention of many scientists, as it is easy to produce using the available resources; it can be produced using a kitchen blender or ultra-sonication energy [8,9]. Nevertheless, exploration of a suitable liquid phase exfoliation system remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the production of large quantities, a cost-effective and environmentally friendly system is very important. Considering this fact, liquid-phase exfoliation has attracted the attention of many scientists, as it is easy to produce using the available resources; it can be produced using a kitchen blender or ultra-sonication energy [8,9]. Nevertheless, exploration of a suitable liquid phase exfoliation system remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…[52,[57][58][59] It has been found that non-aggregated aqueous graphene dispersion with high stability can be obtained using a mechanical method in which the graphite is stirred in the presence of water-soluble bovine serum albumin (BSA). [52,[60][61][62] This method is a suitable alternative for thermal or chemical reduction of graphene oxide and does not require extensive use of cytotoxic chemicals to maintain the aqueous graphene dispersions. [52] Alginate hydrogels have been used to encapsulate astrocytes and alginate/graphene hydrogels have been used to encapsulate dopaminergic neuronal cells; however, to our knowledge, these are the first experiments done that involve encapsulating astrocytes in alginate/graphene microfibers.…”
Section: Introductionmentioning
confidence: 99%
“…However, such promising nanostructure requires additional mechanical and electronic equipment or some typically toxic surfactants to dominate the interfacial interactions between its carbonic layers for employment in cell-encapsulated hydrogels 56,[58][59][60] . A mechanical method based on stirring of graphite in the presence of watersoluble bovine serum albumin (BSA) had been recently reported to produce non-aggregated aqueous graphene solution with high stability 56,[61][62][63] . BSA with positive and negative charged spots could successfully lead to the fabrication of aqueous graphene dispersion and be considered an alternative competent for thermal or chemical reduction of graphene oxide that requires extensive use of cytotoxic chemicals to maintain the aqueous graphene dispersions 56 .…”
Section: Introductionmentioning
confidence: 99%